2022
DOI: 10.3389/fpls.2022.994902
|View full text |Cite
|
Sign up to set email alerts
|

Revealing plant growth-promoting mechanisms of Bacillus strains in elevating rice growth and its interaction with salt stress

Abstract: Soil salinity is a major environmental stress that has been negatively affecting the growth and productivity of rice. However, various salt-resistant plant growth-promoting rhizobacteria (PGPR) have been known to promote plant growth and alleviate the damaging effects of salt stress via mitigating physio-biochemical and molecular characteristics. This study was conducted to examine the salt stress potential of Bacillus strains identified from harsh environments of the Qinghai-Tibetan plateau region of China. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 74 publications
5
25
1
Order By: Relevance
“…The results showed that key genes responsible for membrane transport, osmotic regulation, regulation of reactive oxygen species, cell signalling and fatty acid and lipid metabolism that enable the bacteria to combat with salt stress were mostly detected in NMCN1 and LLCG23, as compared with FZB42. All these genetic features ( SodA, OpuAC, OPuD , OstB, ComA and DegU) previously reported in the literature were known to play an important role in abiotic stress (Cold and Salt) resilience [ 17 , 20 ]. The whole genome genetic analysis of the halophilic strains (NMCN1 and LLCG23) also showed that the selected strains possess a plethora of genes to combat high salinity stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that key genes responsible for membrane transport, osmotic regulation, regulation of reactive oxygen species, cell signalling and fatty acid and lipid metabolism that enable the bacteria to combat with salt stress were mostly detected in NMCN1 and LLCG23, as compared with FZB42. All these genetic features ( SodA, OpuAC, OPuD , OstB, ComA and DegU) previously reported in the literature were known to play an important role in abiotic stress (Cold and Salt) resilience [ 17 , 20 ]. The whole genome genetic analysis of the halophilic strains (NMCN1 and LLCG23) also showed that the selected strains possess a plethora of genes to combat high salinity stress.…”
Section: Discussionmentioning
confidence: 99%
“…and Bacillus spp. isolated from saline soil can promote plant growth under saline conditions [ 6 , 17 ]. This idea has attracted the attention of researchers to discover efficient biotechnological approaches involving the application of PGPR as a bio-resource to reduce salinity effects and enhance plant growth under salt stress [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For JcSAP gene expression patterns in different plant tissues under abiotic stress, the raw expression data of leaf and root tissues subjected to drought stress was retrieved from the public database of NCBI ( ) (accessed on 11 September 2022) under the GEO accession number GSE61109. The expression profiles of all JcSAP genes were exhibited as reads per kilobase per million (RPKM) values and illustrated via heat map using TBtools [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenetic analysis suggested that ZHDs have expanded considerably during angiosperm evolution [ 1 ]. Biotic and abiotic stresses, such as drought, salinity, heavy metals, high temperatures, heat stress, chilling stress, insects, pathogens, mechanical injury, etc., cause severe damage in terms of kmo, plant growth, development, yield, and quality [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. A well-specialized gene network encodes numerous proteins that systematically control plant growth.…”
Section: Introductionmentioning
confidence: 99%